2022
DOI: 10.1002/bse.2979
|View full text |Cite
|
Sign up to set email alerts
|

Green capabilities and green purchasing practices: A strategy striving towards sustainable operations

Abstract: Increasing businesses adverse operations and unsustainable practices are causing rise in environmental concerns. The adoption of green capabilities could be a promising step that can ease environmental problems and achieve green ideology in businesses. In the current study, green capabilities and green purchasing practices were critically theorized and a theoretical framework was developed to address the sustainability problems in supply chain. The data were collected from manufacturing firms located in emergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 82 publications
1
31
0
Order By: Relevance
“…They observed that crude oil affected the transportation sector positively, meanwhile consuming 33% of all energy in the EU. Khan et al ( 2022a ) claimed that the utilization of oil as an integral substance seems to be directly or indirectly linked to all modes of transportation, including roadways, airplanes, and shipping. However, the expansion of all modes of transportation could lead to an increase in crude oil consumption.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…They observed that crude oil affected the transportation sector positively, meanwhile consuming 33% of all energy in the EU. Khan et al ( 2022a ) claimed that the utilization of oil as an integral substance seems to be directly or indirectly linked to all modes of transportation, including roadways, airplanes, and shipping. However, the expansion of all modes of transportation could lead to an increase in crude oil consumption.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Dependence on crude oil products contaminates the environment, generates a high amount of CO 2 , and has harmful effects on urban residents (Kanaboshi et al 2021 ). Besides, crude oil contributes to pollution in the form of toxic gases and hazardous waste, which would then be emitted into the atmosphere (Khan et al 2022a ). The CO 2 emissions are inversely proportional to crude oil consumption.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations